Metallic and ferromagnetic carbon allotrope discovered using molecular precursors - Hong Fang; Joel Therrien; Puru Jena (Physical Review Research, 2025)
Although carbon materials are known for their versatile structures and properties, a crystalline phase of carbon being both metallic and ferromagnetic is yet to be found. Here, using an organic molecular precursor 3,3-dimethyl-1-butene (C_{6}H_{12}) and a comprehensive theoretical study, we have discovered a metastable crystalline carbon phase that is both metallic and ferromagnetic under ambient conditions. The new carbon structures, produced by stacking puckered layers of 4,6-membered rings, are found to exhibit exotic electronic, magnetic, and mechanical properties originating from a special sp^{2}−sp^{3} bonding topology. These findings open the prospect of realizing the metallic and ferromagnetic carbon allotrope in practice.